Effects of immunoglobulin Y-loaded amorphous calcium phosphate on dentinal tubules occlusion and antibacterial activity - Yan, Yanhong; Guan, Yun; Luo, Linjuan; Lu, Bingqiang; Chen, Feng; Jiang, Beizhan (Frontiers in Bioengineering and Biotechnology, 2022)
Aim To evaluate the effects of immunoglobulin Y (IgY)-loaded amorphous calcium phosphate (ACP) (IgY@ACP) on dentinal tubule occlusion and antibacterial activity. Methodology IgY@ACP was synthesized based on a biomimetic mineralization strategy. The structure was examined by transmission electron microscopy and Fourier transform infrared spectroscopy. The IgY release property was assessed in vitro. The cell biocompatibility of IgY@ACP was evaluated by CCK-8. The dentin disks were prepared from healthy human molars, and their dentinal tubules were exposed to EDTA. Subsequently, they were randomly selected and treated with or without IgY@ACP for 7 days. The tubule occlusion morphologies and newly formed layer were observed by scanning electron microscopy (SEM) and x-ray diffraction, respectively. To evaluate the acid resistance and abrasion resistance of IgY@ACP, dentin disks that were treated for 1 day were immersed in acid solution or subjected to a toothbrush. The antibacterial effects against Streptococcus mutans (S. mutans) were evaluated by colony forming units (CFUs) counting, adhesion property assessment, and crystal violet and live/dead bacterial staining. Finally, the occlusion effect was evaluated in rat incisors in vivo. One-way analysis of variance (ANOVA) was performed for statistical analysis. The level of significance was set at 0.05. Results IgY@ACP presented an amorphous phase with a nano size (60-80 nm) and sustained release of protein within 48 h. The CCK-8 results showed that IgY@ACP had good biocompatibility. After treatment with IgY@ACP for 1 day, the majority of dentinal tubules were occluded by a 0.3-μm-thick mineralized layer. Seven days later, all dentinal tubules were occluded by mineralization with a thickness of 1.4 μm and a depth of 16 μm. The newly mineralized layer shown hydroxyapatite-like diffraction peaks. Besides, IgY@ACP had good acid and abrasion resistance. After treatment with IgY@ACP, the CFUs counting and adhesion rate of S. mutans were significantly reduced, the crystal violet staining was lighter, and the S. mutans staining revealed more dead cells. Most importantly, IgY@ACP had a certain occluding property in rat incisors in vivo. Conclusion IgY@ACP can effectively occlude dentinal tubules with acid-resistant stability and has prominent anti-S. mutans effects, rendering it a potentially suitable desensitization material in the clinic.